2020
DOI: 10.1111/jocn.15538
|View full text |Cite
|
Sign up to set email alerts
|

Fear of hypoglycaemia in patients with type 1 and 2 diabetes: a systematic review

Abstract: Aims and objectives To summarise and thematise fear of hypoglycaemia (FOH) in individuals with type 1 diabetes (T1D) and type 2 diabetes (T2D) to provide a theoretical basis for the development of effective interventions. Background FOH is common in this population and can reduce quality of life (QOL) and adversely impact upon diabetes self‐care management. Design A systematic review. Methods Articles published between 2000–2019 were searched in PubMed, MEDLINE, EMBASE, Web of Science and three Chinese databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 58 publications
0
23
0
1
Order By: Relevance
“…One of the important problems observed in patients with type 2 diabetes is FOH (ADA, 2020; SEMT, 2019). FOH impairs the patients’ personal and social life, quality of life, sleep quality, behaviour related to the self‐management of the disease, productivity and compliance with treatment (Zhang et al, 2020). It was demonstrated that hypoglycaemia is responsible for 6%–10% of diabetes‐related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…One of the important problems observed in patients with type 2 diabetes is FOH (ADA, 2020; SEMT, 2019). FOH impairs the patients’ personal and social life, quality of life, sleep quality, behaviour related to the self‐management of the disease, productivity and compliance with treatment (Zhang et al, 2020). It was demonstrated that hypoglycaemia is responsible for 6%–10% of diabetes‐related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Iatrogenic hypoglycemia continues to limit achievement of normoglycemia in T1D [16]. Additionally, fear of hypoglycemia is common in individuals with T1D and parents of children with T1D with significant impact on quality of life [94] and conflicting evidence on glycemic control [95] LGS, including less time spent < 70 mg/dL. PLGS also demonstrates reduction in fear of hypoglycemia and improvements in sleep quality while maintaining stable glycemic control [102].…”
Section: Partial Automation Part 1-hypoglycemia Mitigation the Evolution Of Low Glucose Suspend (Lgs) And Predictive Low Glucose Suspend mentioning
confidence: 99%
“…In one study, 16 people with diabetes in Canada were interviewed about their roles in preventing or self‐managing hypoglycaemia 6,18 . Other studies have focused on the fear of hypoglycaemia or the impact of hypoglycaemia and impaired awareness about hypoglycaemia on the day‐to‐day lives of people with type 1 diabetes and their family members 19–27 …”
Section: Introductionmentioning
confidence: 99%
“… 6 , 18 Other studies have focused on the fear of hypoglycaemia or the impact of hypoglycaemia and impaired awareness about hypoglycaemia on the day‐to‐day lives of people with type 1 diabetes and their family members. 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 Generally, however, primary data regarding the experiences of people with diabetes, including those with type 2 diabetes who use insulin, and their caregivers in managing an SH event are lacking. To address this gap in the literature, the present study explored the experiences during SH events among adults in the United States from the perspectives of both people with diabetes who use insulin and caregivers who assist them in order to inform healthcare providers and in hopes of elevating conversations about SH risk and management.…”
Section: Introductionmentioning
confidence: 99%